Rethinking Cryptocurrency Performance: Downside Risk Evaluation Using Sortino and Calmar Ratios - Reksha Laksana; Erik Nugraha; Hadi Ahmad Sukardi; Agrie Wahyudi Kharisman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study evaluates the investment performance of the 20 largest cryptocurrencies by market capitalization during 2021–2025 using downside risk metrics. A quantitative descriptive approach was applied to 36,500 daily return observations derived from 36,520 daily closing prices obtained from CoinGecko. Performance was assessed using the Compound Annual Growth Rate (CAGR), annualized downside deviation, maximum drawdown, the Sortino Ratio, and the Calmar Ratio, with the risk-free rate set to zero. Descriptive statistics indicate excess kurtosis across all assets and positive skewness in 18 cryptocurrencies, supporting the use of downside-oriented metrics. Only six assets achieved a Sortino Ratio above 1.0, led by SHIB (10.0724), SOL (1.8578), and BNB (1.7341), while only three exceeded a Calmar Ratio of 1.0. Quadrant analysis identified three Alpha Leaders, three High-Yield Fragility assets, and 14 Value Destruction assets. SHIB exhibited a speculative paradox, combining exceptional risk-adjusted performance with a 91.98% maximum drawdown due to its near-zero initial price, whereas LTC was the only asset with negative CAGR. These findings demonstrate that downside risk metrics provide a complementary perspective on cryptocurrency performance by emphasizing downside deviation and drawdown, thereby supporting more informed investment decisions Practically, the resulting downside-based quadrant classification offers investors, market supervisors, and financial educators a concrete tool for distinguishing assets that genuinely reward risk-taking from those that erode capital, thereby strengthening risk-aware decision-making and consumer protection in the crypto-asset market.